Analysis of Service Quality and Hospital Image on Patient Loyalty Influenced by BPJS Kesehatan Patient Satisfaction - Hainun Nisa; Chrismis Novalinda Ginting; Ali Napiah Nasution; Ermi Girsang (Proceeding of the International Conference on Health Sciences and Nursing, 2025)
This research aims to analyze the influence of service quality and hospital image on patient loyalty, with patient satisfaction as an intervening variable, specifically focusing on BPJS Kesehatan patients. Using a quantitative approach, data was collected through surveys distributed to BPJS Kesehatan patients in a hospital setting. Data analysis techniques include descriptive analysis, multiple regression analysis, and path analysis to test the hypotheses. The results indicate that service quality and hospital image significantly affect patient satisfaction, which in turn influences patient loyalty. Patient satisfaction also mediates the relationship between service quality, hospital image, and patient loyalty. These findings provide valuable insights for hospitals in improving service quality and building a positive image to enhance patient satisfaction and loyalty, particularly among BPJS Kesehatan patients.